Program Dakwah untuk Remaja dan Anak-anak Pesisir di Kelurahan Tanah Lemo Bulukumba - Hijrayanti Sari (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2022)
The form of community service as a pillar of the tridarma of higher education and media for developing social intelligence for STIBA Makassar students is in the form of the KKN V STIBA Makassar program which is located on the coast of Lemo Village, Bulukumba Regency through a da'wah approach to early ages and adolescents. Observation of site conditions was carried out using SOAR analysis. Work programs that have been successfully implemented include: BARA (Team Fun Talks), Ramadan Quarantine and Al-Qur'an Education Park (TPA). All activities were successfully carried out and yielded results, namely: the participants became enthusiastic to study Islam more intensively than before. Participants experienced a change in their views on ideals, namely ideals framed by worship. During the Ramadan Quarantine activity, the participants understood the Jurisprudence of Ramadan and became enthusiastic about filling the Ramadan time optimally. While the results of TK/TPA activities are in the form of improving reading and memorizing the Qur'an, reading prayers, and daily prayers.